2016
DOI: 10.1371/journal.pone.0151988
|View full text |Cite
|
Sign up to set email alerts
|

Is IMRT Superior or Inferior to 3DCRT in Radiotherapy for NSCLC? A Meta-Analysis

Abstract: IntroductionThere are no adequate data to determine whether intensity-modulated radiotherapy (IMRT) is superior to three-dimensional conformal radiotherapy (3DCRT) in the treatment of non-small cell lung cancer (NSCLC). This meta-analysis was conducted to compare the clinical outcomes of IMRT and 3DCRT in the treatment of NSCLC.MethodsNo exclusions were made based on types of study design. We performed a literature search in PubMed, EMBASE and the Cochrane library databases from their inceptions to April 30, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…A recently reported meta-analysis of retrospective data assessed the impact of IMRT compared with 3D-CRT on endpoints including overall survival, radiation pneumonitis, and radiation esophagitis 27 . Although IMRT reduced the risk of radiation pneumonitis with a hazard ratio of 0.74 (0.59-0.93), there was an increased risk of radiation esophagitis with a hazard ratio of 2.47 (1.95-3.14).…”
Section: Discussionmentioning
confidence: 99%
“…A recently reported meta-analysis of retrospective data assessed the impact of IMRT compared with 3D-CRT on endpoints including overall survival, radiation pneumonitis, and radiation esophagitis 27 . Although IMRT reduced the risk of radiation pneumonitis with a hazard ratio of 0.74 (0.59-0.93), there was an increased risk of radiation esophagitis with a hazard ratio of 2.47 (1.95-3.14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the US SEER-Medicare data did not find significant differences in survival outcomes between IMRT and 3D-CRT 12,13. A meta-analysis study also reported no significant survival differences 14. However, several single institution studies have reported that IMRT significantly improved the overall survival compared with 3D-CRT in the treatment of non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…This work was focused on CRT which has been reported to be used 2.3 times more frequently than IMRT in NSCLC radiation therapy [25]. Prior to our optimization, beam intensities and aperture shapes were calculated in Eclipse treatment planning system for each respiratory phase, creating deliverable plans.…”
Section: Discussionmentioning
confidence: 99%